Desenvolvimento de um escore preditor da eficácia do tratamento quimioterápico pré-operatório em mulheres com carcinoma de mama localmente avançado - Koga, Katia Hiromoto [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
In order to develop a prediction score of neoadjuvant chemotherapy response, we proposed the breast scintigraphy with 99mTc-sestamibi associated prognostic factors as predictor method. We studied 65 patients diagnosed with ductal carcinoma undergoing breast scintigraphy before neoadjuvant chemotherapy (QT neo), immunohistochemical panel and surgical specimens. The scintigraphic analysis included the development of uptake index made by counts/pixels in identical region of interest under tumor lesion and the reference region in the contra lateral breast and area calculation. The statistical analysis was performed for the total group of patients and separately for groups of AC chemotherapy regimen and ACT. Built a logistic regression model using variables, age, index, tumor location, immunohistochemical panel and axillary nodes, obtaining values predicted according to the complete pathologic response, ROC curve was drawn up, to get score a higher sensitivity and specificity. The area under the ROC curve was significant for all groups and the score obtained was 0.728, 0.834 and 0.667 for the groups total, AC and ACT, respectively. The sensitivity, specificity, and positive and negative predictive values were 81.6%, 81.2%, 93% and 59% for the total group, 75.8%, 90%, 96.1% and 52.9%, for the AC group and 81.3%, 83.3%, 92.8% and 62.5% for the ACT group. The multifactorial prediction score is an effective method for the prediction of neoadjuvant chemotherapy response, since that reflects the biology of the tumor against chemotherapy regimen, early identification of patients who would not benefit from this treatment

Com intuito de desenvolver um escore preditor da resposta quimioterápica neoadjuvante, propusemos a cintilografia de mamas com sestamibi-99mTc, associada a fatores prognósticos como método preditor. Foram estudadas 65 pacientes com diagnóstico de carcinoma ductal submetidas à cintilografia de mamas préquimioterapia neoadjuvante (QT neo), painel imunohistoquímico e avaliação do espécime cirúrgico. A análise cintilográfica compreendeu a elaboração do índice de concentração, com áreas de interesse com contagens/pixels geradas sobre a lesão e na mama contralateral e cálculo da área tumoral. A analise estatística foi realizada para o grupo total de pacientes e separadamente para os grupos de esquema quimioterápico AC e ACT. Construiu-se um modelo de regressão logística utilizando como variáveis, idade, índice, localização do tumor, painel imunohistoquímico e comprometimento axilar, obtendo-se valores preditos que em função da resposta patológica completa foi elaborada uma curva ROC, para conseguir um escore de maior sensibilidade e especificidade. A área da curva ROC foi significativa para todos os grupos e o escore obtido foi de 0,728, 0,834 e 0,667 para o grupos total, AC e ACT, respectivamente. A sensibilidade, especificidade e valores preditivos positivo e negativo foram 81,6%, 81,2%, 93% e 59%, para o grupo total, 75,8%, 90%, 96,1% e 52,9%, para o grupo AC e 81,3%, 83,3%, 92,8% e 62,5%, para o grupo ACT. O escore preditor multifatorial é um método eficaz na predição da resposta quimioterápica neoadjuvante, uma vez, que reflete a biologia do tumor frente ao esquema quimioterápico, identificando precocemente as pacientes que não se beneficiariam deste tratamento
Keywords: Mamas - Cancer - Tratamento; Câncer - Quimioterapia; Diagnóstico imunohistoquímico; Tumores; Breast Cancer